Assessment of mint and pomegranate extracts/oils as antimicrobial agents to inhibit growth of escherichia coli O157:H7 and listeria monocytogenes on shredded carrots - Xylia, Panayiota; Chrysargyris, Antonios; Botsaris, George; Tzortzakis, Nikos G. (My University, 2021)
Among minimally processed vegetables, shredded carrots are particularly popular; however, they are perishable products and can be contaminated throughout the food chain. Chlorine, the most commonly used disinfectant agent in the washing water, fails to reduce the microbial load of fresh produce and furthermore it can adversely affect human health. The aim of this study was to evaluate the antimicrobial activity of different washing treatments with aqueous solutions of mint essential oil (EO) (1:1000) and mint hydrosol (1:10) and pomegranate juice (1:10) against two major food borne pathogens on shredded carrots as well as their effect on carrot’s quality. The results of this study indicate that the tested washing treatments resulted in a small but significant decrease of the microbial load of Escherichia coli and Listeria monocytogenes on the sixth day of storage. Pomegranate juice and mint hydrosol were more effective against L. monocytogenes, whereas mint EO was more effective against E. coli. Furthermore, an increase in carrot’s total phenolics and antioxidants was observed with the application of mint hydrosol and pomegranate juice, whereas mint EO resulted in a decrease on the sixth day of storage. Additionally, a decreased chroma and an increased whiteness index of the shredded carrots were observed during the application of mint hydrosol on the sixth day. Total carotenoids, ascorbic acid, total soluble solids and tritratable acidity were not differ after six days of storage of shredded carrots. Additional efforts are necessary to evaluate and optimize this process.
Keywords: Antibacterial; Antioxidants; Essential oil; Foodborne pathogens; Plant extracts